REVOLUTIONIZING HEALTH MANAGEMENT: THE STRATEGIC INTEGRATION OF SPORTS AND MEDICINE - Ming, Li; Wang, Xiaojie (International Research Journal Diagnostics, 2025)
The integration of sports and medicine is redefining the concept of health management, emphasizing not only the absence of disease but also encompassing psychological, physical, and social adaptability, as well as the pursuit of excellence. This shift in understanding reflects a broader perspective on health that extends beyond traditional boundaries. It acknowledges the economic value of health as a tangible asset, promoting effective human productivity and well-being. This transformation underscores the importance of achieving holistic health and the reciprocal benefits it offers